Viability and Growth of Preantral Follicles Derived from Cryopreserved Ovarian Tissues of a Cheetah (Acinonyx jubatus) Post-mortem - Wongbandue, Grisnarong; Tanpradit, Nae; Thongthainun, Daraka; Thuwanut, Paweena; Chatdarong, Kaywalee (The Thai Journal of Veterinary Medicine, 2013)
This study aimed to investigate freezing effects of ovarian tissues on survival of preantral follicles and observing in vitro growing of preantral follicles retrieved from cryopreserved ovarian cortical tissues of a cheetah post-mortem. After 29-hour cold storage, ovarian cortices were cut into small pieces (2.0 x 2.0 x 1.0 mm3) and allocated to be frozen using a passive cooling container (n = 3 pieces) or vitrification (n=3 pieces). After one year of storage, 43 (10/23) and 21% (12/58) follicles isolated from ovarian tissues cryopreserved using a passive cooling device (slow freezing rate) and vitrification, respectively, were viable (positively stained with neutral red).Thereafter, the viable follicles were in vitro grown in a culture medium containing M199 supplemented with growth hormone (GH), follicular-stimulating hormone (FSH), insulin-like growth factor I (IGF-I)and activin A for 7 days. Diameters and diameter gains were examined on Days 0, 3 and 7. Follicle viability was assessed on Days 0 and 7. Diameters of follicles frozen by the slow freezing decreased gradually from 53.5±14.2 μm on Day 0 to 50.9±17.1μm with 2 out of 10 viables, whereas those frozen using vitrification maintained their diameters between 50.7±15.6 μm and 50.5±17.9 μm on Days 0 and 7, respectively, with 2 of 12 viable. In conclusion, the passive cooling container is suggested to perform a slow freezing rate for ovarian tissue cryopreservation. Although the cheetah ovarian follicles obtained from cryopreserved tissues can be grown in vitro for 7 days, optimization of culture medium is required to improve the viability and growing rate.